How the digital economy promotes urban–rural integration through optimizing factor allocation: theoretical mechanisms and evidence from China - Lu, Yuchen; Zhuang, Jiakun; Yang, Chenlu; Li, Lu; Kong, Mei (Frontiers in Sustainable Food Systems, 2025)
The digital economy plays an increasingly crucial role in bridging the gap between urban and rural areas. This study investigates how the development of the digital economy can foster the integrated development of urban and rural areas by optimizing factor allocation, with an emphasis on its potential to narrow the urban-rural divide. The study aims to examine the impact of the digital economy on urban-rural integration, focusing particularly on the mediating role of optimized factor allocation. Using panel data from 30 Chinese provinces between 2011 and 2022, we construct indicators for digital economy development and urban-rural integration. The analysis employs a two-way fixed-effects model, a mediating effect model, and a spatial Durbin model to explore the spatial evolution and impact of the digital economy on urban-rural integration. Findings suggest that the digital economy enhances urban-rural integration both directly and indirectly. It directly contributes to integration and indirectly optimizes the allocation of labor, capital, land, technology, and information, further promoting urban-rural convergence. The effects of these mechanisms exhibit significant threshold effects and spatial heterogeneity. These results underline the importance of accelerating the digital economy and optimizing factor mobility as key strategies for urban-rural integration. Policy implications focus on enhancing the efficiency of resource allocation across urban and rural areas to accelerate balanced development.